A simple proof of a generalization of eisenstein's irreducibility criterion (1987)
We present a simple proof of Königsberg's Criterion, [K] p.69 and also present families of irreducible polynomials over some fields. In particular, if (n, h) = 1, ao….., an-1 ϵ Z = ring of integers and p is a primer not dividing ao,  then f (x) = xn - ph(ao+a1+…+an-1Xn-1) is irredudible over the rationals. Also if k is any field, then [Formula Matemática].